Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Hannenorak, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Manifestly Haraway - Haraway, Donna Jeanne (University of Minnesota Press, 2016)
"Electrifying, provocative, and controversial when first published thirty years ago, Donna Haraway's "Cyborg Manifesto" is even more relevant today, when the divisions that she so eloquently challenges–of human and machine but also of gender, class, race, ethnicity, sexuality, and location–are increasingly complex. The subsequent "Companion Species Manifesto," which further questions the human-nonhuman disjunction, is no less urgently needed in our time of environmental crisis and profound polarization. Manifestly Haraway brings together these momentous manifestos to expose the continuity and ramifying force of Haraway's thought, whose significance emerges with engaging immediacy in a sustained conversation between the author and her long-term friend and colleague Cary Wolfe. Reading cyborgs and companion species through and with each other, Haraway and Wolfe join in a wide-ranging exchange on the history and meaning of the manifestos in the context of biopolitics, feminism, Marxism, human-nonhuman relationships, making kin, literary tropes, material semiotics, the negative way of knowing, secular Catholicism, and more. The conversation ends by revealing the early stages of Haraway's "Chthulucene Manifesto," in tension with the teleologies of the doleful Anthropocene and the exterminationist Capitalocene. Deeply dedicated to a diverse and robust earthly flourishing, Manifestly Haraway promises to reignite needed discussion in and out of the academy about biologies, technologies, histories, and still possible futures."– Provided by publisher.
Keywords: LGBTQIA2+; animaux de compagnie; approches et analyses; chien; corps; cours; cyberféminisme; cyborg; discipline; discours dominant; identités LGBTQIA2+; lit4700; philosophie; point de vue situé; premier cycle; relations humains/animaux; ressource en ligne; sciences humaines; systèmes d'oppressions; technologie; thématiques

Des sexes innombrables: le genre à l'épreuve de la biologie - Hoquet, Thierry (Éditions du Seuil, 2016)
Combient y-at-il de sexes? "Deux!", répond l'opinion. "Deux" répond la science. Heureuse concordance : c'est donc que l'opinion a raison, conclura-t-on. Mais est-on si certain que l'opinion et la science disent, sur la question du sexe, la même chose? Quand l'opinion affirme qu'il y a deux sexes, elle soutient qu'il existe, dans chaque espèce, deux types d'individus et seulement deux. Il y aurait alors le masculin et le féminin. Mais quand la science avance qu'il y a deux sexes, que vise-t-elle ? Quelle est, pour un biologiste, la signification des termes "mâle" et "femelle" ? En tentant de compter les sexes, on doit bientôt se risquer à distinguer le normal du pathologique.
Section: 1 vol. (249 p.) : ill., couv. ill. en coul. ; 21 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe biologique; sexisme; sexualité; systèmes d'oppressions; thématiques

Notes toward a performative theory of assembly - Butler, Judith (Harvard University Press, 2015)
Judith Butler elucidates the dynamics of public assembly under prevailing economic and political conditions, analyzing what they signify and how. Understanding assemblies as plural forms of perfomative action, Butler extends her theory of performativity to argue that precarity - the destruction of the conditions of livability - has been a galvanizing force and theme intoday's highly visible protests.
Keywords: approches et analyses; corps; discipline; genre; inégalités; militance; performativité; philosophie; précarité; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques

La question du consentement sexuel: entre liberté individuelle et dignité humaine - Simard, D. (Sexologies, 2015)
En matière sexuelle, le consentement est une notion devenue primordiale. Elle permet sur le plan juridique, notamment, de distinguer ce qui ne relève pas du viol et ce qui en relève. C’est toutefois une notion aux contours mal définis, qui donne lieu à des controverses, particulièrement sur la question de la prostitution et sur celle du sadomasochisme pour ce qui concerne l’éthique de la sexualité. Cet article a pour objectif de tenter d’éclairer les termes du débat. Il interroge d’abord les fondements du consentement sexuel, en analysant les différences ou les confusions conceptuelles entre le désir et la volonté, tout d’abord à partir de la lecture des philosophes du XVII e siècle René Descartes et Baruch Spinoza, qui s’opposent sur la place du désir relativement à la raison chez l’être humain, et ensuite du psychanalyste Sigmund Freud, qui introduit l’idée de désir inconscient. L’article montre ensuite comment l’impossibilité d’une liberté absolue, et donc d’un consentement dégagé de toute contrainte, peut conduire certaines organisations féministes à mettre en question le consentement individuel même clairement formulé, et à lui opposer la notion de dignité humaine en un sens transcendant, inspirée du philosophe allemand du XVIII e siècle Emmanuel Kant. Cette notion est interrogée et étudiée dans les cas de la prostitution et du sadomasochisme. L’analyse conceptuelle conduit à mettre en évidence le caractère métaphysique tant de l’approche individualiste du consentement que de l’approche d’inspiration kantienne de la dignité humaine.
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; corps; cours; discipline; europe; phi2030; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

L’« espace public » à l’épreuve de la critique féministe - BENOIT, Audrey (Philonsorbonne, 2014)
On se propose ici d’envisager les limites de la notion habermassienne d’« espace public »1, en interrogeant le problème de sa neutralité axiologique. Le point de vue féministe de Nancy Fraser est à cet égard particulièrement éclairant : il permet de montrer, d’un point de vue interne à la théorie critique, la nécessité d’une reconfiguration conceptuelle de la notion d’« espace public ». Le choix d’une approche féministe pour mener à bien une critique de l’« espace public » comporte un double enjeu : évaluer la portée de cette critique, mais aussi rendre compte de la spécificité féministe de cette critique. Le féminisme interroge en effet l’universalisme délibératif habermassien au prisme des aspects à la fois symboliques et matériels des rapports sociaux de sexe. De plus, si la critique féministe ouvre sur une reconstruction normative de l’« espace public », quelle peut être sa valeur paradigmatique pour d’autres critiques, multiculturalistes ou marxistes, de la notion ?
Keywords: approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; habermas; histoire et politique; judith butler; multiculturalisme; nancy fraser; parité; philosophie; pol4102; premier cycle; rapports sociaux de sexe; sciences humaines; systèmes d'oppressions; thématiques

Traite, prostitution, inégalité - MacKinnon, Catharine A. (M éditeur, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Section: 123 pages ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Engels, Friedrich. « La famille monogamique, ou la grande défaite historique du sexe féminin » dans Philosophie de la famille : communauté, normes et pouvoirs - Radica, Gabrielle (Philosophie de la famille: communauté, normes et pouvoirs, 2013)
Aucune pensée psychologique, morale, sociale, juridique ou politique ne peut faire l’économie d’une étude de la famille, quand bien même elle adopterait des positions individualistes ou libérales. Or quand il s’agit de la famille, l’effort de définition se lie immanquablement à une réflexion normative, car nul ne se contente de dire ce qu’est la famille et chacun croit savoir ce qu’elle devrait être. Les textes cités dans ce recueil, qu’ils proviennent de la philosophie classique (Aristote, Rousseau, Diderot, Kant, Hegel), contemporaine (Okin, Walzer), ou encore de représentants des sciences humaines (Durkheim, Freud, Lenoir, Donzelot), témoignent de ce entrelacement et le questionnent. Que la famille soit considérée comme la plus naturelle des unions, comme une violence faite à la nature, ou comme une construction sociale; qu’elle soit définie comme une société contractuelle ou comme une communauté transcendant l’existence de ses membres : tout cela commande qu’on détermine si cette institution est nécessaire, oppressive et essentiellement hiérarchique, ou si elle peut favoriser certaines formes de liberté et d’égalité; et qu’on dise quels pouvoirs elle subit à son tour et quelle justice elle appelle.
Section: 1 vol. (357 p.) ; 18 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; care; corps; cours; discipline; discours dominant; europe; famille; france; hétérosexualité; mariage; maternité; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Réflexions autour de la notion d’homophobie: succès politique, malaises conceptuels et application empirique - Chamberland, Line; Lebreton, Christelle (Nouvelles Questions Féministes, 2012)
Après en avoir retracé rapidement la genèse, cet article rapporte les principales critiques adressées au concept d’homophobie, notamment son réductionnisme qui tend vers des explications de nature psychologique ainsi que l’éviction de la hiérarchie des sexes/genres. Nous discutons ensuite deux pistes théoriques permettant de contourner les limites précédemment identifiées. La première examine le potentiel de l’approche intersectionnelle. La seconde voie invite à une redéfinition du concept d’homophobie, lui reconnaissant une portée exclusivement descriptive, et non plus en tant que concept explicatif, justifiant ainsi sa subordination au concept d’hétérosexisme qui offre une perspective systémique. Nous examinons ces concepts en fonction de leur capacité à rendre compte de l’oppression des lesbiennes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

« La sexualité des femmes: le plaisir contraint », Nouvelles Questions Féministes, n° 3, 2010 - Guichard-Claudic, Yvonne; Andro, Armelle; Bachman, Laurence; Bajos, Nathalie; Hamel, Christelle (Nouvelles Questions Féministes, 2010)
https://shs.cairn.info/revue-nouvelles-questions-feministes-2010-3-page-4?lang=fr
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; corps; corps féminin; cours; discipline; discours dominant; europe; france; hétérosexisme; intersectionnalité; phi2030; philosophie; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sexualité des femmes*; systèmes d'oppressions; thématiques

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Number: 4
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Mais oui c'est un travail!: penser le travail du sexe au-delà de la victimisation - Parent, Colette; Bruckert, Chris; Corriveau, Patrice; Nengeh Mensah, Maria; Toupin, Louise (Presses de l'Université du Québec, 2010)
La question du travail du sexe fait toujours, aujourd’hui, l’objet de polémiques où le moralisme et les bons sentiments prévalent sur la discussion ouverte. La traite des femmes pour fins de « prostitution » et leur vulnérabilité physique face à la violence et à l’homicide débouchent souvent sur des demandes de répression accrue, et ce sont les travailleuses du sexe qui font les frais de ces discours prohibitionnistes et moralisateurs. Soucieux de véhiculer auprès d’un large public une vision différente de la « prostitution » dans le respect des travailleuses du sexe et de remettre en question les bases du message néo-abolitionniste qui présente ces dernières essentiellement comme des victimes de souteneurs ou de leur fausse conscience, cinq spécialistes ont entrepris la rédaction collective d’un livre pour démystifier plusieurs préjugés liés au travail du sexe. Sont abordés dans ce livre original les fondements du débat actuel de la « prostitution » comme travail, les différentes réponses des régimes juridiques, la variété de pratiques et d’expertises mises en oeuvre par les femmes elles-mêmes, incluant celles des migrantes illégales, et l’action collective des regroupements qui luttent pour une reconnaissance du travail du sexe. Mais oui c’est un travail ! invite donc à déconstruire certains mythes et stéréotypes, et à étayer la preuve à l’effet qu’il est non seulement possible de défendre la légitimité du travail du sexe tout en luttant contre la violence, mais que cela est nécessaire.
Section: xvii, 137 pages ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; phi2030; philosophie; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution

Ces corps qui comptent : de la matérialité et des limites discursives du sexe - Butler, Judith (Éditions Amsterdam, 2009)
Traduction de Bodies That Matter, (1993) La prise en compte de la matérialité des corps n’implique pas la saisie d’une réalité pure, naturelle, derrière le genre : si le sexe est un présupposé nécessaire du genre, nous n’aurons jamais accès au réel du sexe qu’à travers nos schèmes culturels. Le sexe, comme le genre, est une norme culturelle, qui régit la matérialité des corps. Il importe donc de souligner que le concept de matière a une histoire, où sont sédimentés les discours sur la différence sexuelle. En outre, si certains corps (par exemple blancs, mâles et hétérosexuels) sont valorisés par la norme, d’autres (par exemple lesbiens ou non blancs) sont produits comme abjects, rejetés dans un dehors invivable. À travers une reprise critique du concept foucaldien de « contrainte productive », Judith Butler s’efforce, loin de tout volontarisme, de ressaisir la façon dont ces corps peuvent défaire les normes qui les constituent et devenir le lieu d’une puissance d’agir transformatrice. Ce livre, où l’épistémologie se mêle à la politique, constitue un jalon des études de genre et l’un des ouvrages majeurs de son auteure.
Donné en lecture a cours POL4212, « Critically Queer », pp 225-244.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; art contemporain; corps; cours; culture; discipline; fem1000; genre; hétérosexisme; identités LGBTQIA2+; lit4700; maternité; philosophie; pol4212; politique; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe; soc2014; systèmes d'oppressions; thématiques; épistémologie; épistémologie queer; états-unis; études culturelles

Voiles racialisés : la femme musulmane dans les imaginaires occidentaux - Al-Saji, Alia (Les ateliers de l'éthique, 2008)
Cet article étudie deux contextes français dans lesquels les voiles musulmans sont devenus hypervisibles : le débat public qui a mené à la loi française de 2004 interdisant les signes religieux ostensibles dans les écoles publiques, et le projet colonial français de dévoiler les femmes algériennes. Je montre comment le concept de « l’oppression de genre » s’est naturalisé au voile musulman d’une telle manière qu’il justifie les normes de féminités occidentales et cache le mécanisme par lequel les femmes musulmanes sont racialisées. C’est ainsi que le voile devient le point de mire d’un racisme culturel qui se présente comme libérant les femmes musulmanes, un racisme qui semble poser un dilemme au féminisme
Keywords: approches et analyses; corps; cours; discipline; droits des femmes*; europe; fem3400; femmes* musulmanes; france; histoire et politique; phi4336; philosophie; premier cycle; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis